2020
DOI: 10.3390/nano10030441
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic and Oxidative Synthetic Pathways for Highly Efficient PANI-TiO2 Nanocomposites as Organic and Inorganic Pollutant Sorbents

Abstract: Polyaniline (PANI)-materials have recently been proposed for environmental remediation applications thanks to PANI stability and sorption properties. As an alternative to conventional PANI oxidative syntheses, which involve toxic carcinogenic compounds, an eco-friendly procedure was here adopted starting from benign reactants (aniline-dimer and H2O2) and initiated by ultraviolet (UV)-irradiated TiO2. To unlock the full potential of this procedure, we investigated the roles of TiO2 and H2O2 in the nanocomposite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 75 publications
1
27
2
Order By: Relevance
“…In particular, the band at 1500 cm −1 is assigned to benzene rings of PANI, while that at 1600 cm −1 to quinone rings [14][15][16][17]51]. For all the PANI-modified PUs, no signals specifically attributable to titania are recognized, since in the ATR-FTIR spectrum of PANI many bands below 900 cm −1 are observed (Figure S1).…”
Section: Characterization Of the Pt/pu Foamsmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, the band at 1500 cm −1 is assigned to benzene rings of PANI, while that at 1600 cm −1 to quinone rings [14][15][16][17]51]. For all the PANI-modified PUs, no signals specifically attributable to titania are recognized, since in the ATR-FTIR spectrum of PANI many bands below 900 cm −1 are observed (Figure S1).…”
Section: Characterization Of the Pt/pu Foamsmentioning
confidence: 99%
“…It has been demonstrated that PANIs are good candidates for the removal of dyes from the water matrix playing as sorbents, both as powder [14,16,17] and properly supported on different materials [59].…”
Section: Assessment Of Rhb Abatement Capacitymentioning
confidence: 99%
See 2 more Smart Citations
“…From their discovery to date, intrinsically conducting polymers (ICPs) have gradually captured the attention of the scientific community and the industrial world thanks to their outstanding properties that make them interesting for many applications in different sectors, such as supercapacitors [1,2] , sensors [3][4][5][6] , environmental remediation [7][8][9][10] and so on. Among them, polyaniline (PANI) occupies a special place due to its unique ease doping/dedoping process that allows to switch quickly from the insulating form to the conducting one and viceversa.…”
Section: Introductionmentioning
confidence: 99%